IMPLEMENTASI NILAI-NILAI KEPAHLAWANAN IWA KUSUMASUMANTRI DALAM PEMBELAJARAN SEJARAH KELAS XI IPS VI SMAN 1 SINDANGKASIH - Galurawati Candra Pratiwi; Sri Parjiah; Aan Suryana (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2026)
This study aims to describe the history learning process in class XI IPS 6 at SMAN 1 Sindangkasih by implementing the heroic values of Iwa Kusumasumantri in learning. Iwa Kusumasumantri is a national hero who was born in Ciamis, West Java, and is known as a freedom fighter, politician, and intellectual who played a role in the development of the nation. The heroic values discussed include social concern, love for the homeland, discipline, honesty, a love of reading, creativity, and curiosity. The research method used in this study is a qualitative method with a qualitative case study research design. Data collection techniques include observation, interviews, and documentation. The data sources used were primary and secondary data sources. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research results showed that the implementation of Iwa Kusumasumantri's heroic values in history education using the PBL (Problem-Based Learning) model had a positive impact on students. As a result, students become more socially conscious in discussion interactions, disciplined in arriving on time, honest in collaborating, enthusiastic about reading to gather necessary information or data, creative in developing their work, and highly curious. Implementing the heroic values of Iwa Kusumasumantri as a local figure also enhances students' historical awareness